THE COMBINATION OF COLORS IN MUSICAL RAGAS: संगीत के रागों में रंगों का समंवय - Khare, Asha (International Journal of Research -GRANTHAALAYAH, 2014)
Music is considered to be the best in the fine arts. The medium of poetry and music is sound. Sound is the medium to reveal the raga. Raga has a special place in Shabharatiya music. Raga is used in two ways, one is general, the other is special. In the general sense, raga is a sign of pigmentation and in a special sense it signifies a distinct characteristic that is harmonized with the vocal body and the emotional body. Pigmentation means that the raga is pleasant and enjoyable. Nadmya peculiarity means that each raga has a unique distinctive emotional color that sets it apart from the others. A raga is a separate sense that has its own independent and distinct essence compared to other ragas. Bharatamuvan has mentioned Javata singing in his Natyashastra. The raga has been explained by Matangamuvan in his famous treatise Shvrihyadhyasiya. ललित कलाओं में संगीत को श्रेष्ट माना गया है। काव्य एवं संगीत का माध्यम ध्वनि है। ध्वनि ही राग को प्रकट करने वाला माध्यम है। श्भारतीय संगीत में राग का एक विशिष्ट स्थान है। राग का दो अर्थो में प्रयोग हुआ है, एक सामान्य, दूसरा विशेष। सामान्य अर्थ में राग रंजकता का वाचक है और विशेष अर्थ में वह एक ऐसी नादमय विशिष्टता क द्योतक है जो स्वर देह और भाव देह से समन्वित है। रंजकता से तात्पर्य है जो राग सुखद एवं आनन्ददायक है। नादमय विशिष्टता का अर्थ है एक प्रत्येक राग का एक वनजी विशिष्ट भावमय रंग हैए जो उसे दूसरों से पृथक करता है। राग एक पृथक भाव हैए जो अन्य रागों की अपेक्षा अपना स्वतंत्र और विशिष्ट अवस्तत्व रखता है।भरतमुवन ने अपने नाट्यशास्त्र में जावत गायन का उल्लेख वकया है। राग की व्याख्या मतंगमुवन ने अपने प्रवसद्द ग्रंथ श्वृहध्येशिय में की है।